Formulasi Sediaan Sabun Cair Dari Ekstrak Etanol Daun Kersen (Muntingia calabura L.) - Andi Nurpati Panaungi; Hasma Hasma (Journal Syifa Sciences and Clinical Research, 2022)
Cherry leaves (Muntingia calabura L.) is a plant that has many medicinal properties. One part of the plant that is widely used is the leaf which contains flavonoid compounds, saponins and tannins found in cherry leaves so that it has strong antioxidant activity which can be efficacious as skin lightening and antiseptic. This study aims to formulate liquid soap ethanol extract of cherry leaves (Muntingia calabura L.). This type of research was carried out in an experimental laboratory using the maceration method to produce a thick extract from cherry leaves. There were 3 formulas for liquid soap with different extract concentrations, namely FI (3%), FII (6%), and FIII (9%). Tests for liquid soap preparations of cherry leaves extract include organoleptic tests (shape, smell, color), homogeneity test, pH test, foam height test, and water content test. From the results of research conducted on organoleptic tests, FI(3%) has has a liquid form, brown color and a distinctive aroma. and FIII(9%) has a slightly thick liquid form, dark brown color, and a distinctive aroma. In the homogeneity test on all formulas get homogeneous results. In the pH test FI(3%) with a pH of 8, FII(6%) and FIII(9%) with a pH of 9. In the FI(3%) foam height test with a foam height of 8.5 cm, FII(6%) with a foam height 7.7 cm, FIII(9%) with foam height 7.1 cm. on the water content test FI(3%) with a water content of 56.25%, FII(6%) with a water content of 53.75%, FIII(9%) with a water content of 48.00%. So it can be concluded that the liquid soap formulations FI(3%), FII(6%), and FIII(9%) meet the requirements set by SNI in every test of liquid soap preparations. So that cherry leaf extract can be formulated into liquid soap with extract concentrations of 3%, 6% and 9%.